MULTIPLIKASI Aquilaria malaccensis DENGAN NAA DAN RAGI PADA KULTUR IN VITRO - Samanhudi Samanhudi; Amalia Tetrani Sakya; Edi Purwanto; Indah Tri Retnosari (Jurnal Pemuliaan Tanaman Hutan, 2021)
Multiplication of Aquilaria malaccensis with naa and yeast growth regulators on in vitro culture. This study aims to obtain the best concentration of NAA and yeast extract for multiplication of agarwood on in vitro culture. This research was conducted from January to October 2020 at the Laboratory of Plant Physiology and Biotechnology, Faculty of Agriculture, Universitas Sebelas Maret, Surakarta. The experimental design used was a factorial completely randomized design (CRD) with two factors, namely NAA (0 ppm; 0.1 ppm; 0.2 ppm; and 0.3 ppm) and yeast extract (0 mg/l, 700 mg/l, 800 mg/l, and 900 mg/l).(+) The results showed that the combination of 0 ppm NAA and 900 mg/l yeast increased the number of shoots of A. malaccensis explants with the highest average number of 3.67 shoots. A single NAA concentration of 0 ppm was able to increase the number of leaves of explants of A. malaccensis with the highest average leaf rate of 24.5 leaves. A single yeast concentration of 0 mg/l was able to increase the number of leaves of A. malaccensis explants with an average of 22 leaves.